Reduction kinetics of iron ore pellets with coal and coal dust: reduction relation with crystalline phases. Issue 4 (2nd October 2018) - Dwivedi, Deepak
ABSTRACT: Mining sites are source of iron ore fines which can be reduced by coal and coal dust and crystalline phases of iron ore plays important role in this regards. In this experiment, Author validated experimental data with the chemical kinetic model. No significant difference has been observed in the degree of reduction on the type of coal used as the reducing agent. The activation energy was higher (124.71 KJ) while choosing coal as a reducing agent than the coal + coal dust as a reducing agent (59.75 KJ). The highest reaction rate constant was observed at 1000°C. Abnormal swelling was noted at 850 and 900°C, whereas shrinkage was noted at 950 and 1000°C.